Respuesta :
Answer:
constant = -12
Step-by-step explanation:
Let the given equation be
2x² + 8x - 12 = 0 --------(1)
Here B² =(2√2)^2 = 8
Add 8 in both sides of (1)
Step1 : 2x² + 8x + 4 = 12 + 4
Step 2: x² + 4x + 4 = 16
step 3 : x² + 4x + 4 - 16 = 0
Step 4: x² + 4x - 12 = 0 ---(4)
From the (4) we get constant = -12
Answer: 160
Explanation:
2x^2 + 8x - 12 = 0
a = 2 b = 8
Multiply both sides by 4a, or 8.
16x^2 + 64x - 96 = 0
Move the constant to the right side of equation.
16x^2 + 64x = 96
Add b^2 to both sides, or 64. Then factor as a square of a binomial.
16x^2 + 64x + 64 = 96 + 64
(4x + 8)^2 = 160
Please mark brainliest if correct. Hope this helps!